The Role of Super-Atom Molecular Orbitals in Doped Fullerenes in a Femtosecond Intense Laser Field - Hui Xiong (Nature Portfolio, 2017)
Abstract The interaction of gas phase endohedral fullerene Ho3N@C80 with intense (0.1–5 × 1014 W/cm2), short (30 fs), 800 nm laser pulses was investigated. The power law dependence of Ho3N@C80 q+, q = 1–2, was found to be different from that of C60. Time-dependent density functional theory computations revealed different light-induced ionization mechanisms. Unlike in C60, in doped fullerenes, the breaking of the cage spherical symmetry makes super atomic molecular orbital (SAMO) states optically active. Theoretical calculations suggest that the fast ionization of the SAMO states in Ho3N@C80 is responsible for the n = 3 power law for singly charged parent molecules at intensities lower than 1.2 × 1014 W/cm2.